2008
DOI: 10.1093/cvr/cvn255
|View full text |Cite
|
Sign up to set email alerts
|

Larger dispersion of INa in female dog ventricle as a mechanism for gender-specific incidence of cardiac arrhythmias

Abstract: The larger dispersion of I(Na) amplitude within the female cardiac ventricle may contribute to the higher risk of arrhythmias in females. Testosterone modulates this dispersion. By decreasing the transmural dispersion of I(Na), testosterone may exert a protective effect against LQTS-related arrhythmias in males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…23 This together with the fact that I Na is smaller in female vs male ventricular myocytes may explain why AVNRT is more common in female patients in general and in patients with concealed BrS. 24 …”
Section: Brs and Female Sexmentioning
confidence: 99%
“…23 This together with the fact that I Na is smaller in female vs male ventricular myocytes may explain why AVNRT is more common in female patients in general and in patients with concealed BrS. 24 …”
Section: Brs and Female Sexmentioning
confidence: 99%
“…It has also recently been reported that testosterone modulates sodium current dispersion in a canine heart model. 9 In addition, there is evidence that steroid hormones have rapid physiological responses through a non-genomic pathway. Consequently, there is probably a complex interplay of gonadal steroids, genetic and ionic influences.…”
Section: Article P 63mentioning
confidence: 99%
“…Lowe et al reported that INa,L magnitude is higher in female mice compared to males and concluded that this difference contributes to higher arrhythmia susceptibility of females. The increased susceptibility of females to arrhythmias may be further compounded by reduced repolarization reserve and larger intramyocardial inhomogeneity of calcium and potassium currents in females [113][114][115][116][117][118][119][120].…”
Section: Transmural Heterogeneity Of I Nalmentioning
confidence: 99%